Transformative learning in the setting of religious healers: A case study of consultative mental health workshops with religious healers, Ethiopia - Baheretibeb, Yonas; Soklaridis, Sophie; Wondimagegn, Dawit; Martimianakis, Maria Athina (Tina); Law, Samuel (Frontiers in Psychiatry, 2022)
Objective: Psychiatric interventions that consider the socio-cultural and spiritual traditions of patients are needed to address stigma and improve access to mental health services. Approaches that apply tenets of transformative learning hold potential for mitigating an overemphasis on biomedical models and supporting productive collaboration between biomedical practitioners and traditional healers. We present a framework for how to engage in health system reform to enhance mental health services in communities that are distrustful of, or unfamiliar with biomedical approaches. Methods: Transformative learning theory informed the development, implementation, and evaluation of an educational intervention in Ethiopia that aimed to improve delivery of mental health services at Holy water sites. The initiative involved both psychiatrists and traditional healers with lived experience providing care to mentally ill patients. Minutes of stakeholder meetings, workshops and informal interviews with participants were analyzed for evidence of Mezirow’s 11 stages of transformative learning. A participatory action approach was used to encourage practice change. Results: All participants exhibited a high degree of engagement with the intervention and described experiencing disorienting dilemmas. Opportunities to reflect separately and in large groups encouraged a re-examination of attitudes previously contributing to siloed approaches to care and led to instrumental changes in mental health care delivery and a higher degree of coordination and collaboration between psychiatrists and traditional healers. Conclusion: Our study demonstrates the utility of transformative learning theory in both the design and evaluation of initiatives aiming to bridge cross-cultural and cross-professional divides. The learning process was further enhanced by a collaborative participatory action model adjusted to accommodate Ethiopian socio-political and cultural relations.